If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3-x)-2=8
We move all terms to the left:
(3-x)-2-(8)=0
We add all the numbers together, and all the variables
(-1x+3)-2-8=0
We add all the numbers together, and all the variables
(-1x+3)-10=0
We get rid of parentheses
-1x+3-10=0
We add all the numbers together, and all the variables
-1x-7=0
We move all terms containing x to the left, all other terms to the right
-x=7
x=7/-1
x=-7
| 8=−2(x−3) | | 2x•23=27 | | 2x/23x23=27 | | 13+a=4 | | 0=-0.2t^2+18t | | 7x+6=4x+4x | | x+x*1.04=100 | | 6x+6=2x+6+2x+6 | | 224x-16x^2=0 | | x-3x+2.5=(x-3)^2+^0.5(x-18) | | 15x+11=8x+1+8x+1 | | x=0.255(x+5) | | 0.07−0.003x=0.1 | | 2(x-5)+1=1+x | | 9s=8s−8 | | A=-2+3a+8 | | 4x−x=15 | | 56-6x=4x+15 | | 32u=12.8 | | –2v=9+7v | | -4x+2x=9-10 | | 3(x-2)^2-8=40 | | 9t(2t-4)=25 | | 8x-2x=11+9 | | F(x)=90(1.36) | | 4y=-16/3 | | 10/p=7/9 | | 4b-8b=-4 | | -3.5=k2.8 | | 8x+31.45=55.45 | | 5x-2=6x-18 | | 3x-5+2x-15=x |